1978
DOI: 10.1111/j.1440-1681.1978.tb00684.x
|View full text |Cite
|
Sign up to set email alerts
|

Brain Biogenic Amines and Intravenous Self‐adminstration of Cocaine in Rats

Abstract: 1. The possible involvent of noradrenaline, dopamine, serotonin and 5-hydorxyindoleacetic acid in the behavioural reinforcement produced by invravenous cocaine has been investigated. 2. rats, in Skinner boxes, were allowed to self-administer cocaine through a chronically implanted jugular vein cannula. A consistent response rate in the order of one self-administration every 10 min was observed with a dose of 3.0 mg/kg cocaine hydrochloride per response. 3. Another group of rats was cannulated and injected with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1981
1981
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The drug is readily self-administered (Hill and Powell 1976; Roberts et al 1977; Ross et al 1978; see reviews by Gawin 1988; Johanson 1988), produces preferences for places associated with its administration (Mucha et al 1982; Mueller and Stewart 2000; Spyraki et al 1982b; for review, see Tzschentke 2007) and reduces brain stimulation thresholds (Ahmed et al 2002; Markou and Koob 1991; 1992). Müller and colleagues (2008) have suggested that these initial positive effects of cocaine might be attributable, at least in part, to short-lived anxiolytic effects of drugs.…”
Section: Introductionmentioning
confidence: 99%
“…The drug is readily self-administered (Hill and Powell 1976; Roberts et al 1977; Ross et al 1978; see reviews by Gawin 1988; Johanson 1988), produces preferences for places associated with its administration (Mucha et al 1982; Mueller and Stewart 2000; Spyraki et al 1982b; for review, see Tzschentke 2007) and reduces brain stimulation thresholds (Ahmed et al 2002; Markou and Koob 1991; 1992). Müller and colleagues (2008) have suggested that these initial positive effects of cocaine might be attributable, at least in part, to short-lived anxiolytic effects of drugs.…”
Section: Introductionmentioning
confidence: 99%
“…The rewarding and reinforcing effects of morphine can be modeled in laboratory animals using several behavioral conditioning techniques, including drug self-administration (Ross et al 1978; Wilson et al 1971), conditioned place preference (CPP) (Mucha et al 1982), and intracranial self-stimulation (ICSS) (Kornetsky and Bain 1992; Olds and Milner 1954). Intracranial self-stimulation is an operant behavioral method that measures the value of electrical stimulation (brain stimulation reward or BSR) applied to the fibers of the medial forebrain bundle (MFB) at the level of the lateral hypothalamus, and can be used to assess the reward-potentiating or reward-devaluing effects of a drug (Olds and Milner 1954; Wise 1998).…”
Section: Introductionmentioning
confidence: 99%